Continuous non-invasive blood pressure during continuous repositioning by pulse transit time. Issue 1 (31st December 2016) - Jeong, Hieyong; Yoshimoto, Kayo; Wang, Tianyi; Ohno, Takafumi; Yamada, Kenji; Kido, Michiko; Ohno, Yuko
Abstract: The purpose of the present study was to propose a method to measure continuous non-invasive arterial pressure (CNAP) of severely handicapped patient during continuous repositioning. We have been interested in healthcare for severely handicapped children. Although their long stay in hospital could be led to a circulatory disorder or a serious secondary disease, there was little way to give an adequate healthcare service for them due to several kinds of side effects. Thus, we developed the non-invasive sensor system to measure pulse transit time (PTT) through the different output signal between the two different measuring points. The proposed extended model of algorithm enabled us to measure continuous blood pressure (BP) with the measured PTT. The algorithm considered the influence of gravity on BP; there was no need to re-tune the system even if the posture of patient was changed. We performed the continuous repositioning experiment from the supine posture to 45 or 75° postures after the effectiveness of the proposed algorithm was confirmed. Through experimental results, it was found that the proposed method has the strongest correlation with commercial BP device. The experimental results showed that it was possible for the proposed algorithm to measure CNAP during continuous repositioning without the re-tune of system. It was recommended that some points of developed prototype hardware were necessary to be improved and the integration of other bio signals was more helpful for providing important insight into the overall physical condition.